A natural history study of nitrous oxide versus propofol‐assisted intrathecal therapy in the treatment of acute lymphoblastic leukemia. Issue 8 (10th March 2022) - Miller, Lane H.; Winter, Stuart S.; Watson, Dave; Livingston, Mylynda; Nemata, Resty; Messinger, Yoav
Abstract: Background: Childhood acute lymphoblastic leukemia (ALL) treatment requires numerous lumbar punctures (LPs) with intrathecal (IT) chemotherapy to prevent and treat central nervous system disease. Historically, LPs in this setting are performed using propofol sedation at most institutions. At our center, LPs are often alternatively performed under nitrous oxide (N2 O). To date, there have been no large‐scale assessments comparing these sedation methods for this purpose. Procedures: Retrospective cohort study of patients aged 0–31 years with ALL treated between January 1, 2013 and December 31, 2018 at the Children's Minnesota Cancer and Blood Disorders Center, including all therapeutic LPs performed in the clinic setting under either propofol or N2 O. Results: Among 215 patients and 2677 therapeutic LPs, 56.6% ( n  = 1515) occurred under N2 O, with 43.3% ( n  = 93) of patients using exclusively N2 O with all LPs. The incidence of traumatic LPs (red blood cell [RBC] ≥10 cells/μl) was similar between both treatments (27.3% vs. 30.2%). Successful IT chemotherapy delivery (99.7% N2 O vs. 99.8% propofol) did not differ between sedation types. Experiencing a traumatic LP under N2 O was associated with a sedation switch for the subsequent LP (adjusted odds ratio [aOR] 2.40, p  = .002), whereas older age (aOR 1.08, p  < .0001) and higher body mass index (BMI) percentile (aOR 1.01, p  = .009) were associated with increased likelihood for undergoing a traumatic LP. Conclusion: N2 O is an effective sedation option for therapeutic LPs in children with ALL with noninferiority to propofol in terms of IT chemotherapy administration and traumatic LP incidence. For many patients, N2 O can effectively replace propofol during LP procedures, which has important safety and quality‐of‐life implications.